The Association of Circumcision and Genitourinary Cancer, Especially Penile Cancer and Prostate Cancer: A 30-Year Systematic Review and Meta-Analysis - Surya, Prima Ardiansah; Putratama, Alfin; Surya, Radika Naufal Hadi; Ananda, Gede Yogi Prema (http://dharmais.co.id/, 2024)
Background: The relationship between genitourinary cancer and circumcision has been debated for a long time. Two types of genitourinary cancer that are often discussed in relation to circumcision are penile cancer and prostate cancer. Methods: A systematic review was conducted on the Science Direct database and Perish with the following databases: Pubmed, Google Scholar, and Crossref. Case-control studies were assessed with the Newcastle-Ottawa Scale. Meta-analysis was performed on penile cancer in situ, invasive penile cancer, and prostate cancer. Meta-analysis of proportions was carried out on penile cancer. Results: 10 studies were analyzed for penile cancer and prostate cancer, and 9 studies were analyzed for penile cancer proportion. Total OR in circumcision and penile cancer in situ (OR = 0.90; 95% CI 0.48–1.69; p = 0.74). Total OR in circumcision and invasive penile cancer (OR = 1.04; 95% CI 0.27–3.94; p = 0.95). Total OR in circumcision and prostate cancer (OR = 0.97; 95% CI 0.79–1.19; p = 0.78). The uncircumcised proportion among penile cancer cases (0.82; 95% CI 0.60–0.97). Conclusions: There was no significant relationship between circumcision and genitourinary cancer. Malignant cells in penile cancer and prostate cancer occur due to a chronic inflammatory process.